Shaw, Á., & Yanushevskaya, I. (2021). Students' views and experiences of the training and use of phonetic transcription in speech and language therapy: the Irish perspective - Yanushevskaya, Irena (My University, 2021)
Phonetic transcription is an essential skill for practising SLTs required during the assessment, diagnosis and management of clients with speech difficulties Student SLTs must receive appropriate training to carry out phonetic transcription accurately and reliably once out in the workforc
ICPLA 2021
Keywords: Phonetic transcription; STUDENT EXPERIENCE